(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: most hepatitis A viral infections in children are asymptomatic or have mild non specific manifestations but some are complicated. Objective: to evaluate all cases of hepatitis A viral infection in children who were admitted over one year period and enlighten out the abnormal presentations and predict complications. Patients and methods: during the period from 1st of June 2005- 1st of June 2006, fifty cases of hepatitis A viral infection (who had hepatitis A virus IgM +ve) were studied and analyzed regarding the clinical presentations, coarse of the illness, complications and outcome. Results: fifty patients enrolled in the study, with male to female ratio of 1.8:1 and 32 (64%) of them presented in the age of 1-5 years. Fulminant hepatic failure was found in 7 (14%) cases, 5 (10%) had prolonged cholestasis , 5 (10%) had exacerbation of pre- existing chronic liver disease, 2 (4%) had recurrent or relapsing hepatitis A viral infection, and 5 (10%) cases had extra hepatic manifestations , 3 (6%) were G6PD deficient patients who had sever hemolysis. Conclusions: hepatitis A viral infection can present in different ways. The level of consciousness, presence of ascites and severely abnormal biochemical and hematological values were of great help in predicting complicated cases of hepatitis A viral infection. Key words: hepatitis A, abnormal presentations, children.